2015
DOI: 10.1186/s13002-015-0060-0
|View full text |Cite
|
Sign up to set email alerts
|

The uses of Kenyan aloes: an analysis of implications for names, distribution and conservation

Abstract: BackgroundThe genus Aloe is renowned for its medicinal and cosmetic properties and long history of use. Sixty-three Aloe species occur in Kenya, of which around 50 % are endemic. Several species of aloes are threatened with extinction and knowledge about their use is of major importance for sound conservation strategies. The main aims of this study were to assess the biocultural value of Aloe in Kenya by documenting local uses of aloes and evaluating how the vernacular names reflect the relative importance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…In Kenya, the leaf decoction of A. rabaiensis is traditionally claimed by Maasai to heal enlarged spleen (Bjorå et al, 2015). For instance, a survey conducted on the ethnomedical practice by inhabitants around Lake Jipe in Tanzania revealed that A. rabaiensis sap is used to treat diarrhoea related diseases in human and livestock.…”
mentioning
confidence: 99%
“…In Kenya, the leaf decoction of A. rabaiensis is traditionally claimed by Maasai to heal enlarged spleen (Bjorå et al, 2015). For instance, a survey conducted on the ethnomedical practice by inhabitants around Lake Jipe in Tanzania revealed that A. rabaiensis sap is used to treat diarrhoea related diseases in human and livestock.…”
mentioning
confidence: 99%
“…Furthermore, A. americana is one of the plants most cultivated as a live fence in the Andes (Carlson & Añazco 1990), which would contribute to its high number of medicinal uses that it has. Due to its availability, there would be more opportunities to experiment with new medicinal applications for this species (Stepp & Moerman 2001, Bjorå et al 2015. F. andina is also a versatile plant, although to a lesser extent because its "heart" is considered too narrow to obtain mishki.…”
Section: Discussionmentioning
confidence: 99%
“…Different ethnic groups in Africa recognize their most-valued Aloe at the genus level as "the aloe" and add explanatory names for the other species, such as the "spotted aloe" and the one-legged aloe. [233] Plant is heavily used as medicinal purposes by pastoral and agro-pastoral communities living in African, Asian and European dry ecoclimatic regions. [234] In India, plant is traditionally used by many ethnic groups for various household and medicinal purposes.…”
Section: Ulcerative Colitismentioning
confidence: 99%